Answer:
[tex]f(x)^-^1=\sqrt[3]{\frac{x+9}{4}}[/tex]
Step-by-step explanation:
Finding the inverse of a function is essentially doing a given function in backwards order. An easy trick to doing such is to treat the evaluation (f(x)) like a variable. Think of the function as an equation, then solve the function for (x) in terms of (f(x)).
[tex]f(x)=4x^3-9[/tex]
Inverse operations,
[tex]f(x)=4x^3-9\\\\(f(x))+9=4x^3\\\\\frac{((f(x))+9)}{4}=x^3\\\\\sqrt[3]{\frac{(f(x))+9}{4}}=x[/tex]
Now put this in the form of an inverse function, switch the places of the terms (x) and (f(x)), remember to indicate that it is an inverse function,
[tex]f(x)^-^1=\sqrt[3]{\frac{x+9}{4}}[/tex]